A comprehensive evaluation of single nucleotide polymorphisms associated with osteosarcoma risk: A protocol for systematic review and network meta-analysis. Issue 26 (26th June 2020) - Ye, Zhuo-Miao; Luo, Ming-Bo; Zhang, Chi; Zheng, Jing-Hui; Gao, Hong-Jun; Tang, You-Ming
Abstract: Background: Single nucleotide polymorphisms (SNPs) have been inconsistently associated with osteosarcoma (OS) risk. This meta-analysis aimed to synthesize relevant data on SNPs associated with OS. Methods: Databases were searched to identify association studies of SNPs and OS published through January 2020 from the databases of PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure, the Chinese Science and Technology Periodical Database, and Wan fang databases. Network meta-analysis and Thakkinstian algorithm were used to select the most appropriate genetic model, along with false positive report probability for noteworthy associations. The methodological quality of data was assessed based on the STrengthening the REporting of Genetic Association Studies statement Stata 14.0 will be used for systematic review and meta-analysis. Results: This study will provide a high-quality evidence to find the SNP most associated with OS susceptibility and the best genetic model. Conclusions: This study will explore which SNP is most associated with OS susceptibility. Registration: INPLASY202040023. Abstract : Supplemental Digital Content is available in the text